A new model for analyzing antimicrobial peptides with biomedical applications - Beschin, Alain; Bilej, M. (Amsterdam : IOS ; Tokyo : Ohmsha, 2002)
This volume first presents evidence for the earthworm's immune system; the results strongly suggest that certain molecules of the earthworm's immune system may be exploited as natural antibiotics - thus the biomedical applications.
Preface; Contents; Introduction to the Earthworm Immune System; Coelomocytes (Leukocytes); Antimicrobial Activity and Cytotoxicity; Other Annelid Models: Leeches; Other Invertebrate Models; Mitogenic, Lectin and Cytokine-like Activities; Activities against Parasites; Summary and Perspectives; Bibliography of Edwin L. Cooper emphasizing on earthworms (1966-2002); Author Index.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Peptide antibiotics -- Congresses; Earthworms -- Congresses; Biomedical engineering; Antimicrobial Cationic Peptides -- analysis; Biomedical Engineering; Annelida -- immunology; Biomedical Technology; Antibiotiques peptidiques -- Congrès.; Génie biomédical.; biomedical engineering; SCIENCE -- Life Sciences -- Zoology -- Invertebrates; Peptide antibiotics; Earthworms; Biomedical engineering; Earthworms; Peptide antibiotics; Antibactériens.; Invertébrés -- Immunologie -- Congrès.; Antibiotiques peptidiques -- Congrès.; Congress; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings; Actes de congrès.